Beyond the Egg and the Sperm?: How Science Has Revised a Romance through Reproductomics. (November 2022) - Lamoreaux, Janelle
Social scientists have shown that scientific characterizations of the egg and the sperm are shaped by gender stereotypes and cultural values. How have such characterizations been transformed by a recent embrace of -omics, when studies of reproduction increasingly go beyond genomics to incorporate proteomics, transcriptomics, exposomics, and other -omics perspectives? Scientists studying reproduction and analyzing eggs, sperm, and embryos are in some ways reimagining the roles, identities, and functions of gametes as fundamentally shaped by other molecular entities and environments. Such relational understandings of substances and processes, however, continue to operate through a teleology that often conscripts more nuanced -omics reflection into familiar genomic visions of sex and reproduction. While ideas of the gene as an alienable object may be unraveling, -omics efforts to go beyond the egg and the sperm are frequently constricted by an understanding of reproduction that remains tied to individualized bodies and by a genomically infused interpretation of the gamete as life itself.